Surface electromagnetic waves on boundary between lossy dielectric and left-handed material with gain - Galaydych, V.K.; Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2017)
It was studied the properties of surface electromagnetic waves that propagate along the interface between the semi-infinite lossy dielectric medium and the left-handed material with “gain”. It was assumed that both media are isotropic. The dispersion curves of the eigenmodes of such waveguide structures were obtained. It was shown that for the different modes of waveguide structure there are different quantities and ratios of left-handed material with “gain” required to compensate for wave energy losses in the dielectric. Изучены свойства поверхностных электромагнитных волн, распространяющихся вдоль границы раздела полубесконечных диэлектрика с потерями и левостороннего материала с «усилением». Предполагалось, что обе среды являются изотропными. Получены дисперсионные зависимости для собственных мод такой волноведущей структуры. Показано, что для различных рассматриваемых мод структуры существуют различные величины и соотношения «усиления» левосторонней среды, которые необходимы для компенсации потерь энергии волны в диэлектрике. Вивчено властивості поверхневих електромагнітних хвиль, що поширюються уздовж межі розділу напівнескінченних діелектрика з втратами і лівостороннього матеріалу з «підсиленням». Вважалось, що обидва середовища є ізотропними. Отримано дисперсійні залежності для власних мод такої хвилеводної структури. Показано, що для різних розглянутих мод структури існують різні величини та співвідношення «посилення» лівостороннього середовища, що необхідні для компенсації втрат енергії хвилі в діелектрику.